Networks of nations the evolution, structure, and impact of International Networks, 1816-2001 - Maoz, Zeev (Structural analysis in the social sciences, 2011)
"Zeev Maoz offers a novel perspective on the study of international relations as a system of interrelated networks that co-evolve and interact with one another"--